1990
DOI: 10.1159/000293307
|View full text |Cite
|
Sign up to set email alerts
|

Turner’s Syndrome – Review of the Literature with Reference to a Successful Pregnancy Outcome

Abstract: A 30-year-old Japanese female with Turner’s syndrome had become pregnant and delivered a normal male infant by cesarean section. Her menarche was at age 14, and secondary sex characteristics developed normally. She had some features of Turner’s syndrome, and cytogenetic studies from peripheral blood lymphocytes and several tissues revealed only 45, XO karyotype without evidence of mosaicism. To our knowledge, she is only the thirteenth case of monosomy X to achieve pregnancy. A review of the literature indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 12 publications
1
33
0
3
Order By: Relevance
“…15,241 One series indicated that the risk for an abnormal pregnancy outcome in women with nonmosaic Turner syndrome could be as high as 50%, when taking into account miscarriage and stillbirth. 242 An earlier study had reported both on both fetal wastage (22/46), and chromosome abnormalities among liveborns (8/26), including 3 with trisomy 21. 243 Amniocentesis should be offered to women with Turner syndrome who conceive.…”
Section: Reproduction and Genetic Counselingmentioning
confidence: 99%
“…15,241 One series indicated that the risk for an abnormal pregnancy outcome in women with nonmosaic Turner syndrome could be as high as 50%, when taking into account miscarriage and stillbirth. 242 An earlier study had reported both on both fetal wastage (22/46), and chromosome abnormalities among liveborns (8/26), including 3 with trisomy 21. 243 Amniocentesis should be offered to women with Turner syndrome who conceive.…”
Section: Reproduction and Genetic Counselingmentioning
confidence: 99%
“…Fertility is poor, however, and unassisted pregnancy occurs in only 2–4% of women [13, 26]. Of these, approximately one third end in spontaneous abortion or perinatal death, and a further third have chromosomal abnormalities, particularly Down’s or Turner’s, and congenital malformations [26, 27]. These figures are probably subject to publication bias and the outlook may improve with prospective monitoring, but genetic counselling at present should strike a balanced note of caution.…”
Section: Clinical Manifestations Of Turner Syndrome In Adultsmentioning
confidence: 99%
“…Assisted reproduction has recently offered an opportunity for women with TS to become pregnant and bear children successfully. In many countries, oocyte donation is now a treatment option for infertility in TS women [3, 11, 12], but its success is conditional upon the development of a mature uterus [13, 14]. Thus, height gain and uterine development are apparently the two most important quality-of-life issues for adult women with TS.…”
Section: Introductionmentioning
confidence: 99%